Cover Feature: Entering the Augmented Era: Immersive and Interactive Virtual Reality for Battery Education and Research (Batteries & Supercaps 11/2020). Issue 11 (14th October 2020) - Franco, Alejandro A.; Chotard, Jean‐Noël; Loup‐Escande, Emilie; Yin, Yinghui; Zhao, Ruijie; Rucci, Alexis; Ngandjong, Alain C.; Herbulot, Simon; Beye, Benjamin; Ciger, Jan; Lelong, Romain
Abstract : The Cover Feature illustrates a Virtual Reality headset bringing a novel immersive and interactive tool for battery technology education and research. More information can be found in the Concept by A. A. Franco and co‐workers .